2013
DOI: 10.3109/21681805.2013.860189
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide treatment in patients with metastatic castration-resistant prostate cancer progressing after chemotherapy and abiraterone acetate

Abstract: Previous abiraterone therapy is associated with a less marked fall in PSA following enzalutamide therapy in post-chemotherapy mCRPC patients compared with reported results in randomized trials. Larger prospective studies of sequencing are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 12 publications
3
44
0
Order By: Relevance
“…Expression of AR splice variants in CTCs was also recently associated with primary resistance to abiraterone or enzalutamide (27) although AR amplification was not evaluated in this study, which may be significant since fulllength AR is typically coexpressed with AR-V7 (28) and may be required for tumor growth mediated by AR splice variants (29). Nevertheless, it is likely that divergent aberrations of the AR underpin cross-resistance between different novel agents targeting the androgen-AR axis (30)(31)(32)(33)(34)(35)(36)(37), as exemplified by our observation that AR exon 8 mutations were mutually exclusive with AR copy number gain in 73% of cases. With this in mind, real-time serial analysis of circulating biomarkers, including cfDNA, could aid optimal therapy sequencing for individual patients.…”
Section: Discussionmentioning
confidence: 89%
“…Expression of AR splice variants in CTCs was also recently associated with primary resistance to abiraterone or enzalutamide (27) although AR amplification was not evaluated in this study, which may be significant since fulllength AR is typically coexpressed with AR-V7 (28) and may be required for tumor growth mediated by AR splice variants (29). Nevertheless, it is likely that divergent aberrations of the AR underpin cross-resistance between different novel agents targeting the androgen-AR axis (30)(31)(32)(33)(34)(35)(36)(37), as exemplified by our observation that AR exon 8 mutations were mutually exclusive with AR copy number gain in 73% of cases. With this in mind, real-time serial analysis of circulating biomarkers, including cfDNA, could aid optimal therapy sequencing for individual patients.…”
Section: Discussionmentioning
confidence: 89%
“…[31][32][33][34][35][36][37][38] Data seem to show a blunted effect of each after the use of the other, suggesting cross-resistance. It remains unclear which patients benefit from one agent as the first agent compared with the other.…”
Section: Sequential Therapy Using Asismentioning
confidence: 99%
“…For treatment sequences involving enzalutamide or abiraterone as a second-line agent following the opposite agent, several other studies have reported that 17-28% of patients achieved a PSA response. [26][27][28][29][30][31][32][33][34] A report from Schnadig et al showed that more patients reached a third-line treatment if they received docetaxel followed immediately by cabazitaxel, compared to docetaxel followed by abiraterone. 35 This retrospective analysis in 667 post-docetaxel mCRPC patients showed that 31% of patients who received cabazitaxel second-line received abiraterone in third-line, compared to only 12% of patients who received cabazitaxel third-line if they received abiraterone second-line.…”
mentioning
confidence: 99%